IDENTIFIKASI KANDUNGAN BORAKS DAN FORMALIN PADA CILOK DI KELURAHAN KERTOSARI KABUPATEN BANYUWANGI: Identificatin of Borax and Formalin in Cilok from Kertosari Village Banyuwangi Regency - Eko Agung Purnomo; Rosiana Ulfa; Arfiati Ulfa Utami (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2023)
In Indonesia today, especially in Banyuwangi, food with a high level of safety has begun to be difficult to find, especially in market snacks, one of which is cilok. Many cilok traders are naughty by using non-food preservative additives in their processed products with the aim of increasing shelf life and getting a chewy texture without adding a lot of meat. The slot gacor 777 preservatives are borax and formalin. This study was conducted to determine the presence or absence of borax and formalin content in cilok in Kertosari Village, Banyuwangi Regency with the turmeric extract method and KMnO4. The results showed that there was not one sample that was positive for containing borax or formalin, but there was one sample whose color was slightly whitened, but there was little possibility of formalin content in it.